A dance with fate - Marillier, Juliet (Marillier, Juliet. Warrior Bards, 2020)
"A young woman who is a bard-and a warrior-seeks to repay her debts and settle scores in this thrilling historical fantasy series. The young warrior and bard Liobhan has lost her brother to the Otherworld. Even more determined to gain a place as an elite fighter, she returns to Swan Island to continue her training. But Liobhan is devastated when her comrade Dau is injured and loses his sight in their final display bout. Blamed by Dau's family for the accident, she agrees to go to Dau's home as a bond servant for the span of one year. But Oakhill, she soon learns, is a place of dark secrets. The vicious Crow Folk still threaten both worlds. And Dau, battling the demon of despair, is not an easy man to help. When Liobhan and Dau start to expose the rot at the center of Oakhill, they place themselves in deadly danger. For their enemy wields great power and will stop at nothing to get his way. It will take all the skills of a Swan Island warrior and a touch of the uncanny to give them a hope of survival. . . "--